SVG essentials : producing scalable vector graphics with XML - Eisenberg, J. David, ....- (Sebastopol (Calif.) : O'Reilly, 2002)
Samenvatting:Scalable Vector Graphics Â-- or SVG -- is the new XML-based graphicsstandard from the W3C that will enable Web documents to be smaller,faster and more interactive. This insightful book takes you through theins and outs of SVG, from the basics to more complicated features.Whether you're a graphic designer looking for new tools, or a programmercreating and managing graphics, this book provides a solid foundation
Keywords: Computer graphics; Programmeren; SVG (Document markup language).; Web sites -- Design; Www world wide web